2016
DOI: 10.1159/000443423
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Stenting Associated With Improvement in Renal Function and Blood Pressure Control in Long-Term Follow-Up

Abstract: Background/Aims: Clinical benefits of percutaneous treatment of renal artery stenosis (RAS) remain controversial. The aim of this study was to evaluate the effects of renal artery stenting on kidney function and blood pressure (BP) control in the log-term follow-up. Additionally angiographic follow up was performed in selected subgroup of patients. Methods: The study was designed as international registry of 265 consecutive patients with RAS treated with renal artery stenting. The primary end-point of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Since glomerular filtration rate (GFR) is difficult to measure, GFR is calculated from the serum concentrations of endogenous filtration markers, which is called estimated glomerular filtration rate (eGFR) [14-16]. As a surrogate parameter for renal function, eGFR has been widely used in the diagnosis and clinical management of CKD [14-25]. To date, studies on the relationship between PWV and renal function have yielded inconsistent results [17-24].…”
Section: Introductionmentioning
confidence: 99%
“…Since glomerular filtration rate (GFR) is difficult to measure, GFR is calculated from the serum concentrations of endogenous filtration markers, which is called estimated glomerular filtration rate (eGFR) [14-16]. As a surrogate parameter for renal function, eGFR has been widely used in the diagnosis and clinical management of CKD [14-25]. To date, studies on the relationship between PWV and renal function have yielded inconsistent results [17-24].…”
Section: Introductionmentioning
confidence: 99%
“…Renal function may improve in approximately half of patients who undergo renal artery revascularization, whereas approximately one third may experience progression of kidney disease (13). Patients with lower baseline eGFR or rapidly declining kidney function may show a greater response to stent placement than patients with normal or near-normal kidney function, as seen in previous randomized control trials (11,14,15). Rates of progression to RRT after renal stent placement have been reported to be approximately 10%-20% among patients with CKD (16,17).…”
Section: Discussionmentioning
confidence: 81%
“…The findings in the present study indicate that, for patients with advanced CKD, the risk for RRT and all-cause mortality will decrease with each unit of eGFR increase. Patients with renal insufficiency from renal artery stenosis and intact compensatory mechanisms such as sustained hypertension may benefit more from revascularization (11). This may explain the lack of benefit from renal artery stent placement demonstrated in the CORAL trial (4), in which patients had better baseline kidney function as well as questionable anatomic and no hemodynamic assessment of the significance of renal artery stenosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective and prospective observational studies reported the benefits of renal artery revascularization in terms of blood pressure decrease and renal protection in patients with ARAS ≥50% [26, 27] even when this was associated with uncontrolled hypertension [28-30]. In a registry of 265 patients with angiographic evidence of ARAS ≥50%, a subgroup of whom had uncontrolled systolic hypertension, average blood pressure fell in a follow-up of 2 years from 160/86 mm Hg to 135/75 mm Hg [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a registry of 265 patients with angiographic evidence of ARAS ≥50%, a subgroup of whom had uncontrolled systolic hypertension, average blood pressure fell in a follow-up of 2 years from 160/86 mm Hg to 135/75 mm Hg [28]. Approximately half of patients in the registry had improved glomerular filtration suggesting that renal revascularization could preserve renal function in a substantial proportion.…”
Section: Discussionmentioning
confidence: 99%